PEMBENTUKAN KEPRIBADIAN OLEH GURU MELALUI PENDIDIKAN KARAKTER DI SMA PUSPITA KABUPATEN BANYUASIN - Hari Arkani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
In this article, Teacher is a Profession who prepares human resources to meet the nation’s development in filling Independence. Teachers with all their abilities and effort to prepare learning for learners. So it is not wrong if we put a teacher as one of the keys for developments of nation develop nation in the future. Shaping personality through character of education is absolutely necessary, by following the figures who are worthy of being followed. This article took a descriptive qualitative research. This research provided an overview of the students’ character and gave the solutions in character based learning for students in Banyuasin regency, especially for Senior high school students in Puspita Air Kumbang Banyuasin regency. To get the data the researcher used observation, interviews, and documentations. The results this study explained that in Senior high school Puspita Air Kumbang Banyuasin regency, the students love their homeland very much, responsibility, dicipline, reading interest, religious, environment cares, spirit of nationalism and friendship. Therefore, teachers had an important role in character building of nation.